Accuracy of intraoperative bone registration and stereotactic boundary reconstruction during total knee arthroplasty surgery. Issue 1 (16th September 2022) - Herregodts, Stijn; Vermue, Hannes; Herregodts, Jan; De Coninck, Bert; Chevalier, Amélie; Verstraete, Matthias; De Baets, Patrick; Victor, Jan
Abstract: Background: The intraoperative registration of the bones play a crucial role in image‐based computer‐assisted knee arthroplasty to achieve accurate implant placement and to create reliable stereotactic bone boundaries for robot‐assisted surgical systems. Method: This study assessed the intraoperative registration accuracy on six intact fresh frozen cadavers. Results: Rotational errors around the mechanical axis were the largest, with a standard deviation of 1.2° and outliers up to 3.7°. The mean translational errors were lower than 1 mm, with outliers up to 1.5 mm. These errors were amplified to 2 mm for the registration‐based reconstruction of the posterior bone surface at the resection levels. Conclusion: Given the cumulative behaviour of surgical errors, registration errors can affect the final implant positioning. Furthermore, inaccuracies in the reconstructed bone boundary directly affect the virtual stereotactic boundaries used in robotic‐assisted surgery and can result in an incomplete resection or inadvertent soft tissue damage.